Differential degradation patterns of photovoltaic backsheets at the array level. (15th March 2018) - Fairbrother, Andrew; Boyd, Matthew; Lyu, Yadong; Avenet, Julien; Illich, Peter; Wang, Yu; Kempe, Michael; Dougherty, Brian; Bruckman, Laura; Gu, Xiaohong
Graphical abstract: Highlights: Field survey and degradation analysis of non-fluoropolymer-based PV backsheets. Observation of unique, non-uniform patterns of backsheet degradation within an array. Linkage of backsheet degradation to gradient light exposure conditions. Determination of significant array design factors which affect degradation. Abstract: There are relatively few field studies on the degradation of non-fluoropolymer-based backsheets, and understanding their in-field behavior is critical for further development of such products. In this study, backsheet degradation of modules with one of these new types of backsheets (polyethylene naphthalate (PEN)-based) was documented at a four-year old utility-scale array located in Maryland (USA). Visual inspection, colorimetry, glossimetry, and Fourier-transform infrared spectroscopy (FTIR) revealed highly varied properties depending on module position within the array. Specifically, modules near the edge of the array and with higher mounting elevations underwent greater amounts of backsheet degradation, as indicated by yellowing and gloss-loss. The reason for these unique degradation patterns were differential backside exposure conditions, especially of ultraviolet light. This was strongly influenced by the array design, including array structural and environmental factors, such as module spacing and ground cover, respectively. Within the array, no clear link between backsheet degradation and module output or safety has been identified. However, such a relationship may be expected to become more pronounced with time, affecting system lifetime and ultimately the levelized cost of electricity (LCOE). The observed phenomena have implications for both backsheet product development and array design, especially for modules that utilize newer classes of non-fluoropolymer-based backsheets which are typically more susceptible to environmental degradation.